Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.ebiom.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 106b and 222 Improve Hyperglycemia in a Mouse Model of Insulin-Deficient Diabetes via Pancreatic β-Cell Proliferation

Abstract: Major symptoms of diabetes mellitus manifest, once pancreatic β-cell numbers have become inadequate. Although natural regeneration of β-cells after injury is very limited, bone marrow (BM) transplantation (BMT) promotes their regeneration through undetermined mechanism(s) involving inter-cellular (BM cell-to-β-cell) crosstalk. We found that two microRNAs (miRNAs) contribute to BMT-induced β-cell regeneration. Screening murine miRNAs in serum exosomes after BMT revealed 42 miRNAs to be increased. Two of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 39 publications
4
73
0
1
Order By: Relevance
“…Next, we used miRanda to identify the target genes of these piRNAs and identified 630 genes. GO enrichment analysis identified five genes, namely, acyl‐CoA oxidase 1 ( ACOX1 ), V‐kit Hardy‐Zuckerman 4 feline sarcoma viral oncogene homolog, Fc fragment of IgG‐binding protein ( FCGBP ), androgen receptor ( AR ), and receptor tyrosine kinase‐like orphan receptor 2 ( ROR2 ) (Figure A). WEGO analysis indicated that these five genes played different roles in spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we used miRanda to identify the target genes of these piRNAs and identified 630 genes. GO enrichment analysis identified five genes, namely, acyl‐CoA oxidase 1 ( ACOX1 ), V‐kit Hardy‐Zuckerman 4 feline sarcoma viral oncogene homolog, Fc fragment of IgG‐binding protein ( FCGBP ), androgen receptor ( AR ), and receptor tyrosine kinase‐like orphan receptor 2 ( ROR2 ) (Figure A). WEGO analysis indicated that these five genes played different roles in spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Spermatogenesis is a complex process involving mitosis and meiosis. Sperm formation depends on the expression and regulation of several genes such as KIT at different stages . KIT is an important gene in germline stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, intravenous administration of artificial miR‐106b‐5p and miR‐222‐3p mimics associated with atelocollagen as a carrier also promoted post‐injury β‐cell proliferation. The therapeutic miRNAs targeted and downregulated the cyclin dependent kinase (CDK) interacting protein/kinase inhibitory protein (CIP/KIP) family of cell cycle repressors, resulting in increased β‐cell mass and a better control of glycaemia (Table ). These data suggest that extracellular delivery of miRNAs mediated by inert carrier molecules is an alternative strategy to the use of the exosomes themselves.…”
Section: Exosomes As Therapy For Diabetesmentioning
confidence: 99%